ASUPAN ENERGI DAN PROTEIN SERTA GANGGUAN GIZI BERDASARKAN TINGGI BADAN / UMUR PADA ANAK DENGAN PALSI SEREBRAL DI RUMAH SAKIT HAJI MEDAN - SUCI AULIYAH SIREGAR; NURCAHAYA SINAGA (JURNAL ILMIAH SIMANTEK, 2021)
Cerebral palsy is a motor disorder due to non-progressive brain damage that occurs during a child's development. It may beassociated with comorbidities such as malnutrition (46% - 90% of patients), impaired growth, mental retardation, epilepticseizures, communication disorders, visual and auditory disabilities, and gastrointestinal symptoms, such as dysphagia, andconstipation. To determine nutritional disorders in children with cerebral palsy at Haji Hospital Medan. This research isdescriptive with a prospective cohort approach and uses 30 respondents from Cerebral Palsy patients seen from medicalrecords and food recall. It was found that the results of the description of energy and protein intake and nutritional status ofchildren with cerebral palsy were very short as many as 12 people. The results of the food recall in children with cerebralpalsy were mostly in the category of low calorie intake as many as 24 people and the category of protein intake being less asmany as 20 people.